FC 084LIPOTOXICITY MEDIATED BY GPR43 ACTIVATION CONTRIBUTES TO PODOCYTE INJURY IN DIABETIC NEPHROPATHY THROUGH MODULATING ERK/EGR1 PATHWAY. (29th May 2021) - Lu, Jian; Zhang, Jia Xiu; Chen, Pei Pei; Li, Xue Qi; Liu, Bicheng; Ma, Kun Ling
Abstract: Background and Aims: The G-protein-coupled receptor 43 (GPR43) is a post-transcriptional regulator involved in cholesterol metabolism. Our previous studies demonstrated that intracellular cholesterol accumulation contributed to podocyte injury in diabetic nephropathy (DN). This study aimed to investigate possible roles of GPR43 activation in lipid nephrotoxicity in DN and to explore its potential mechanisms. Method: The experiments were conducted by using diabetic GPR43 knockout mice and cell culture model of podocytes. Renal pathological changes were checked by periodic acid schiff staining, immunohistochemical staining and transmission electron microscopy (TEM). The lipid deposition and free cholesterol contents in kidney tissues were detected by Oil Red O staining, BODIPY staining, and cholesterol quantitative assay. The protein expressions of GPR43, LC3II, p62 and related molecules of LDLR pathway in kidney tissues and podocytes were detected by real-time PCR, immunofluorescent staining, and Western blotting. Results: There were decreased plasma level of LDL-cholesterol and cholesterol accumulation in kidney tissues of diabetic GPR43 knockout mice. In vitro study demonstrated that acetate, a stimulator of GPR43, increased LDLR-mediated cholesterol uptake in podocytes, accompanied with reduced cholesterol autophagic degeneration, characterized by inhibited LC3 maturation, p62 degradation, and autophagosome formation. These may evoke synergistic effects attributing to cellular cholesterol accumulation in podocytes. While genetic knockdown or pharmacological inhibition of GPR43 inhibited this effect in podocytes. Furthermore, the activation of GPR43 led to the activation of ERK1/2/EGR1 pathway in podocytes, whereas blocking ERK1/2 activity or reducing EGR1 expression reversed cholesterol influx and the inhibition of autophagy mediated by GPR43 activation in podocytes. Meanwhile, deletion of the GPR43 improved autophagy and inhibited the ERK1/2-EGR1 pathway of podocyte in diabetic mice in vivo . Conclusion: Activation of the GPR43 mediated lipid nephrotoxicity contributes to podocyte injury in DN, which was mainly through the activation of ERK/EGR1 pathways. These findings suggested that the GPR43 receptor could be a potential therapeutic target for the prevention of DN progression.